FORMULATION AND NUTRITIONAL EVALUATION OF HIGH-FAT DIET FEED FOR FATTY LIVER INDUCEMENT IN RODENT MODELS - Putri Anggreini; Jutti Levita; Hadi Kuncoro; Andi Tenri Kawareng; Sri Adi Sumiwi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Non-alcoholic fatty Liver Disease (NAFLD) is one of the most prevalent lipid disorders worldwide. In the pursuit of drug discovery and development, animal modeling is crucial to elucidate the mechanisms underlying a disease. One form of animal model of NAFLD involves the induction of a high-fat diet (HFD). However, most HFDs exhibit complexity in the formulation, and commercial HFDs tend to be costly. This study aimed to formulate an HFD feed with minimal ingredients that are capable of inducing liver steatosis. This study commenced with the development of 4 dietary formulations (F1, F2, F3, and F4) comprising various food components with specific proportions and treatments. A proximate analysis was conducted for each formulation. Subsequently, the most promising formulation was administered to the rats for 14 days. On day 15, liver organs were harvested for histological analysis. The results showed that among the four formulations developed, HFD F4 exhibited the best physical appearance and nutritional proximate components, characterized by its stability in form and high fat (41.8%), high protein (21.5%), and low carbohydrate (23.2%) content. Histology examination revealed that two weeks of administration of F4 administration led to severe degeneration, inflammation, and necrosis in rat hepatocytes compared to the normal group (p < 0.001), thus confirming that HFD F4 may be developed as an inducer of steatosis in rats. Keywords: experimental animal model; high-fat diet; liver steatosis ; NAFLD